Report. On-farm Experimentation Workshop, 13th September, 2023. - Adolwa, Ivan; Muthamia, Joses; Lutomia, Cosmas Kweyu; Cook, Simon E.; Nchanji, Eileen (2023)
1-day workshop (9:00-17:30), morning session was for presentations on OFE or OFE-related experiences R NUTCAT OFE case study, CIAT HER+ case study, One Acre Fund case study, followed by interactive sessions with participants in the late morning and early afternoon sessions (Define customer profile, value map and review value proposition), and finally feedback and conclusion R 41 attendees = 15 farmers and 9 organisations (OCP-Africa, APNI, Kenya Agricultural Livestock Research Organization (KALRO), Tupande by One Acre Fund, Cereal Growers Association (CGA), University of Nairobi, Pwani University, County Government extension, and the Alliance of Bioversity International and CIAT)